Entrenchment in usage-based theories : what corpus data do and do not reveal about the mind - Blumenthal-Dramé, Alice (Topics in English linguistics, 2012)
This book explores the usage-based claim that high usage frequency leads to the entrenchment of complex words in the minds of language users. To probe the correlation between corpus-extracted usage data and mental entrenchment, the author operationalises entrenchment in Gestalt psychological terms and conducts a series of behavioural and neuroimaging experiments.